The mediating role of impulsivity between sleep quality and suicidal ideation in adolescent population: a multicenter cross-sectional study in the northeastern Sichuan, China - Zhong, Yunling; He, Jinlong; Luo, Jing; Zhao, Jiayu; Cen, Yu; Wu, Yuhang; Song, Yuqin; Lin, Cen; Pan, Lu; Luo, Jiaming (Frontiers in Psychiatry, 2024)
Suicidal ideation is a critical early stage in the progression towards suicidal be havior. Prior research has established links between sleep quality,impulsivity,and suicidal tendencies,yet the interaction among these factors has been less explor ed.This study aims to explore the mediating role of impulsivity in the relations hip between sleep quality and suicidal ideation in adolescents.Employing a cros s-sectional study design, 6,974 questionnaires were distributed,including the Soci o-demographic Characteristics Questionnaire,Barratt Impulsiveness Scale,the Posit ive and Negative Suicide Ideation Inventory,and the Pittsburgh Sleep Quality In dex Scale.The participants were high school and middle school students from 3 3 schools in northeastern Sichuan, China, selected through random cluster samp ling. Of these 6,786 questionnaires were analyzed.The participant distribution in cluded 47.2% male and 52.8% female students,with 68.3% from junior schools and 31.7% from senior schools.The prevalence of suicidal ideation was found to be 13.6%.The analysis, which involved correlation analysis and the construct ion of a structural equation model,revealed that sleep quality had a significant